PEMANFAATAN FUNGI Aspergillus flavus, Aspergillus terreus, DAN Trichoderma harzianum UNTUK MENINGKATKAN PERTUMBUHAN BIBIT Bruguiera gymnorrhiza - M. Luthfi Dharmawan; Yunasfi Yunasfi; Mohammad Basyuni (Peronema Forestry Science Journal, 2015)
Condition of mangrove area has been decreasing due to the degradation and conversion of mangrove for other land use. Therefore, it is necessary for rehabilitation on mangrove land. This study aimed to test the ability of various types fungi on a field scale then to compare the ability of fungi to increase the growth of mangroves and to establish a type of fungi that have a greater ability to promote the growth of mangroves.  B. gymnorrhiza seed was used with 4 treatments. The results showed a response Bruguiera gymnorrhiza seedlings treated with the fungi Aspergillus flavus applications, Aspergillus terreus, and Trichoderma harzianum effect on seedling growth. T. harzianum showed the best results compared to other fungi on all parameters of observation with an average height of 10,45 cm, an average diameter of 0,56 cm, average leaf area rat 104,87 cm2, and the total dry weight of 2, 65 g. All parameters observed fungal applications only affected on height growth and total dry weight significantly on B. gymnorrhiza seedlings.Keywords: Bruguiera gymnorrhiza, mangrove, rehabilitation, Trichoderma harzianum